Effects of a complex intervention on fall risk in the general practitioner setting: a cluster randomized controlled trial - Freiberger E (Dove Medical Press, 2013)
Ellen Freiberger,1 Wolfgang A Blank,2 Johannes Salb,1 Barbara Geilhof,3 Christian Hentschke,1 Peter Landendoerfer,2 Martin Halle,3 Monika Siegrist31Institute of Sport Science and Sport Universität Erlangen-Nürnberg, Nuremberg, Germany; 2Institute of General Practice, Technische Universität München, Munich, Germany; 3Department of Prevention, Rehabilitation and Sports Medicine, Technische Universität München, Munich, GermanyPurpose: To study the feasibility of first, reaching functionally declined, but still independent older persons at risk of falls through their general practitioner (GP) and second, to reduce their physiological and psychological fall risk factors with a complex exercise intervention. We investigated the effects of a 16-week exercise intervention on physiological (function, strength, and balance) and psychological (fear of falling) outcomes in community-dwelling older persons in comparison with usual care. In addition, we obtained data on adherence of the participants to the exercise program.Methods: Tests on physical and psychological fall risk were conducted at study inclusion, and after the 16-week intervention period in the GP office setting. The 16-week intervention included progressive and challenging balance, gait, and strength exercise as well as changes to behavioral aspects. To account for the hierarchical structure in the chosen study design, with patients nested in GPs and measurements nested in patients, a three-level linear mixed effects model was determined for analysis.Results: In total, 33 GPs recruited 378 participants (75.4% females). The mean age of the participants was 78.1 years (standard deviation 5.9 years). Patients in the intervention group showed an improvement in the Timed-Up-and-Go-test (TUG) that was 1.5 seconds greater than that showed by the control group, equivalent to a small to moderate effect. For balance, a relative improvement of 0.8 seconds was accomplished, and anxiety about falls was reduced by 3.7 points in the Falls Efficacy Scale–International (FES-I), in the intervention group relative to control group. In total, 76.6% (N = 170) of the intervention group participated in more than 75% the supervised group sessions.Conclusion: The strategy to address older persons at high risk of falling in the GP setting with a complex exercise intervention was successful. In functionally declined, community-dwelling, older persons a complex intervention for reducing fall risks was effective compared with usual care.Keywords: complex exercise intervention, functional declined community-dwelling older persons